Fracture-seepage characteristic zones of the overburden of extra-thick coal seams: Evolutionary patterns and their engineering applications - Xiangguo KONG; Tianshuo ZHAO; Haifei LIN; Pengxiang ZHAO; Xu WANG; Yuchu CAI; Pengfei JI; Di HE; Ke LI; Chuanyu XU (Meitian dizhi yu kantan, 2025)
Objective and Methods Given that the overburden’s structure significantly influences pressure relief gas extraction, this study aims to explore the gas migration patterns of the overburden of thick coal seams during coal seam mining. To this end, this study analyzed the evolutionary patterns of the fracture morphology and seepage capacity of the overburden using physical similarity simulation experiments. Accordingly, this study investigated the mechanisms behind the evolution of fracture-seepage characteristic zones of the overburden of extra-thick coal seams and proposed a method for identifying fracture-seepage characteristic zones of the overburden. Using this method, this study conducted gas extraction along the experimental mining face based on directional boreholes. Results and Conclusions The results indicated that the bed separation and fracture density of the central part of the overburden were 47% and 31%, respectively, of those of its two sides, indicating that both indicators were low in the central part and high on the two sides. In the early stage of mining, the fracture-seepage characteristics of the overburden displayed synchronous spatial distributions. With the further advancement of the working face, the overburden was affected by mining to varying degrees, gradually displaying evolutionary zoning. Specifically, the central part of the overburden exhibited significantly weaker fracture-seepage characteristics than the surrounding areas, with these characteristics of the two sides gradually weakening with an increase in the horizon. The overburden manifested fracture ratios, fracture entropy, connectivity coefficients, and permeability ranging from 1.0% to 8.5%, from 0.15 to 0.90, from 0.10 to 0.65, and from 6.34×10−9 m2 to 7.78×10−7 m2, respectively. Based on the impacts of the fractures and seepage capacity of the overburden on gas migration, the overburden can be divided into four zones: a low-elevation turbulence zone, a medium-elevation compaction zone, a medium-elevation transition zone, and a high-elevation constant flow zone. Based on the spatiotemporal evolution patterns of the fracture ratios, fracture entropy, connectivity coefficients, and permeability of these zones, this study developed an evolution model and identification flowchart for the fracture-seepage characteristic zones of the overburden of extra-thick coal seams. The analysis of the evolution model reveals that the medium-elevation transition zone and the high-elevation constant current zone were the dominant horizons for gas extraction, with the vertical distances of boreholes designed ranging from 6 m to 25 m. The changes in the pure gas flow extracted from boreholes can be divided into three stages: the initial fluctuation, rapid growth, and slow drop stages. The mining along the mining face yielded methane volume fractions of less than 1%, suggesting encouraging effects in the engineering practice. This verifies the feasibility of the proposed method and the rationality of directional borehole arrangement. The results of this study will provide some theoretical guidance for the optimization of borehole parameters for gas extraction and the gas control of coal seams.